The Chinese-English Conference Interpreting Corpus: Uses and Limitations - Hu, Kaibao; Tao, Qing (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
This paper presents an overview of the compilation of the Chinese-English Conference Interpreting Corpus followed by an outline of research findings based on data obtained from the corpus. It is argued that interpreting corpora, including the Chinese-English Conference Interpreting Corpus, are called to play an increasingly important role in the study of linguistic features of interpreted texts, interpreting norms and the cognitive process of interpreting. Research based on the Chinese-English Conference Interpreting Corpus suggests that the use of English passive construction, optional connective ‘that’ and the infinitive particle ‘to’ in interpreted texts is demonstrably more frequent than in the translated English texts of the Chinese government’s work reports and the non-translated English texts of press conferences. In a broader sense, interpreted texts exhibit greater tendency towards normalization and explicitation than written translated texts. This paper also touches on the limitations that have been observed while working with interpreting corpora. These limitations are in a large measure related to the difficulty in transcribing nonverbal aspects of the interpreting activity, including the speaker’s tone and facial expressions, as well as the audience’s facial expressions. These aspects have a clear effect on interpreter’s choice/use of interpreting strategies and methods, so they merit careful consideration in interpreting studies.